Optimization of gold–palladium core–shell nanowires towards H2O2 reduction by adjusting shell thickness. Issue 2 (16th January 2020) - Dong, Yongdi; Chen, Qiaoli; Cheng, Xiqing; Li, Huiqi; Chen, Jiayu; Zhang, Xibo; Kuang, Qin; Xie, Zhaoxiong
Abstract : Aurich Pd@AuPdrich core–shell nanowires with tunable shell-thickness are successfully synthesized via a one-pot route and they show optimized H2 O2 detection activity. Abstract : Designable bimetallic core–shell nanoparticles exhibit superb performance in many fields including industrial catalysis, energy conversion and chemical sensing, due to their outstanding properties associated with their tunable electronic structure. Herein, Au–Pd core–shell (Aurich Pd@AuPdrich ) nanowires (NWs) were synthesized through a one-pot facile chemical reduction method in the presence of cetyltrimethyl ammonium bromide (CTAB) surfactant. The thickness of the Pd shell could be adjusted by directly controlling the Au/Pd feeding ratio while maintaining the nanowire morphology. The as-obtained Au75 Pd25 core–shell NWs with a thin Pdrich shell showed significantly enhanced activities towards the reduction of hydrogen peroxide with the sensitivity reaching 338 μA cm −2 mM −1 and a linear range up to 10 mM. In sum, Pd shell thickness could be used to adjust the electronic structure, thereby optimizing the catalytic activity.